Accurate and Rapid Identification of Candida spp. Frequently Associated with Fungemia by Using PCR and the Microarray-Based Prove-it Sepsis Assay - Aittakorpi, Anne (American Society for Microbiology, 2012)
The rapid identification of microbes responsible for bloodstream infections (BSIs) allows more focused and effective therapies and outcomes. DNA sequence-based methods offer an opportunity for faster, accurate diagnosis and for effective therapy. As our objective of the study, the ability of the Prove-it Sepsis platform, already proven as a rapid PCR- and microarray-based assay for the majority of sepsis-causing bacteria, was extended to also rapidly identify clinically relevant yeasts in blood culture. The performance characteristics of this extended platform are described. We found that the extended diagnostic Prove-it Sepsis platform was found to be highly accurate when analyzing primary isolates, spiked blood cultures, nucleic acid extracts from a retrospective blood culture data set, and primary blood cultures. Comparison of the blood culture results from the Prove-it Sepsis platform with those from conventional culture-based methods or by gene sequencing demonstrated a sensitivity of 99% and a specificity of 98% for fungal targets (based on analysis of a total of 388 specimens). Total assay time was 3 h from DNA extraction to BSI diagnosis. These results extend the performance characteristics of the Prove-it platform for bacteria to the easy, rapid, and accurate detection and species identification of yeasts in positive blood cultures. Incorporation of this extended and rapid diagnostic platform into the tools for clinical patient management would allow possibly faster identification and more focused therapies for BSIs.